Use Of English Through Image Media To Earlychildhood Group B (5-6) - Tantia, Aulia Faraz; Mukhtar AH, Nurkamelia (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Based on the results of observations in the field that the use of children's English has not developed optimally, so it is necessary to use English picture media. This experimental study aims to determine the use of English through pictures to group B (5-6) years at Babussalam Kindergarten, Pekanbaru. The subjects of this study were the teachers and children of group B in Babussalam Kindergarten. The population of this study amounted to 30 children, while the sample of this study was group B children (5-6) years which consisted of 12 children. Data collection techniques used observation, documentation and formal tests. This research design uses one group pretest-posttest with t-test or the test has the formula tcount > ttable. If tcount is greater than ttable, then H0 is rejected and Ha is accepted using the SPSS Windows version 22 program. The data shows that H0 is rejected and Ha is accepted. To find out how much the use of English picture media for children in group B at Babussalam Kindergarten Pekanbaru is used the normalized gain formula and obtained from the results of the formula is 88.76% which is included in the category which is in the high category. So it can be concluded that there is an influence on the use of English picture media to group B children in Babussalam Kindergarten Pekanbaru.